Lack of uniform diagnostic criteria for inflammatory breast cancer limits interpretation of treatment outcomes: a systematic review [corrected] [published erratum appears in CLIN BREAST CANCER 2008 Feb;8(1):25]. - Kim T; Lau J; Erban J (Clinical Breast Cancer, 2006)
PURPOSE: Inflammatory breast cancer (IBC) is the most aggressive type of breast cancer. No randomized controlled trial or systematic review with an IBC-only cohort that evaluates interventions has been published. We conducted a systematic review of the literature to characterize the reporting of clinical criteria and response to neoadjuvant therapy for IBC. PATIENTS AND METHODS: We searched MEDLINE and other sources for the following: previously untreated patients with IBC without metastasis in cohort studies; utilized chemotherapy; and reported clinical outcomes. The following 4 groups were analyzed: no anthracycline induction, low-dose anthracycline induction, moderate-dose anthracycline induction, and high-dose chemotherapy requiring stem cell support. Weighted averages for the overall response rates were calculated using a random effects model. RESULTS: Twenty-seven studies met all criteria, totaling 1232 patients. Clinical description of IBC eligibility criteria and reported response assessments varied significantly among studies. The response rates and 3- and 5-year overall survival for all 27 studies ranged from 14% to 100%, 22% to 84%, and 32% to 75%, respectively. Pathologic complete response rates after no anthracycline induction, low-dose anthracycline induction, moderate-dose anthracycline induction, and neoadjuvant high-dose chemotherapy subgroups were 4% (95% confidence interval [CI], 1%-18%), 11% (95% CI, 7%-17%), 14% (95% CI, 8%-22%), and 32% (95% CI, 24%-41%), respectively. CONCLUSION: The criteria and reporting of IBC and treatment response was notably variable, with significant potential for subject heterogeneity. Pathologic complete response rates appear to be related to intensity of neoadjuvant treatment; however, this analysis is not based on randomized data. Future clinical trials should define and report the criteria for IBC diagnosis and response assessment to enhance interstudy comparisons.